The Influence of Individual Characteristics and Non-Physical Work Environment on Employee Performance - Fidiya, Fidiya; Santi Nururly; Embun Suryani; Ala`a Nimer AbuKhalifeh; Anton R. Sabella (Tinta Emas Publisher, 2025)
This study aims to determine the effect of individual characteristics and non-physical work environment on the performance of employees at the Praya Tengah Sub-District Office. The population in this study consists of all employees at the Praya Tengah Sub-District Office, with the sampling technique using purposive sampling. This type of research is associative quantitative research. Data processing in this study used SPSS 26.0, where validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, significance tests (t-test), and determination coefficient tests (R Square) were conducted. The results of this study show that the non-physical work environment has a greater influence on employee performance at the Praya Tengah Sub-District Office. Based on the t-test results, it was found that t count > t table (1.993 > 1.697) or the significance value (0.026 < 0.05), indicating that the non-physical work environment has a positive and significant effect on the performance of employees at the Praya Tengah Sub-District Office.